The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1365-2109.2002.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of soybean, linseed and marine oils on aerobic gut microbiota of Arctic charrSalvelinus alpinusL. before and after challenge withAeromonas salmonicidassp.salmonicida

Abstract: Populations of heterotrophic bacteria present in the hindgut region of Arctic charr Salvelinus alpinus L. fed dietary soybean, linseed and marine oils before challenge with Aeromonas salmonicida ssp. salmonicida and marine oil after challenge were estimated using the dilution plate technique. There were differences in bacterial composition between the rearing groups before and after challenge, as well as interindividual variations. For example, carnobacteria were only isolated from the hindgut region of fish f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 44 publications
2
46
0
3
Order By: Relevance
“…Neste caso, seria de relevante importância lembrar que condições de estresse (Olsen et al, 2005), estágio reprodutivo (Silva et al, 2005), idade (Bates et al, 2006), mudanças abruptas na dieta bem como a adição de certos componentes nesta exerceram influências muitas vezes negativas sobre a densidade populacional na microbiota intestinal, com alterações também nos gêneros dos micro-organismos componentes dela (Ringo e Olsen, 1999;Ringo et al, 2002;Refstie et al, 2006).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Neste caso, seria de relevante importância lembrar que condições de estresse (Olsen et al, 2005), estágio reprodutivo (Silva et al, 2005), idade (Bates et al, 2006), mudanças abruptas na dieta bem como a adição de certos componentes nesta exerceram influências muitas vezes negativas sobre a densidade populacional na microbiota intestinal, com alterações também nos gêneros dos micro-organismos componentes dela (Ringo e Olsen, 1999;Ringo et al, 2002;Refstie et al, 2006).…”
Section: Discussionunclassified
“…Nestas, foram encontrados com maior frequência micro-organismos cocoides e leveduriformes. A predominante presença de bactérias cocoides também foi relatada no trabalho de Ringo e Olsen (1999) e Ringo et al (2002). Austin e Al-Zahrani (1988) relataram dificuldades na detecção da presença de leveduras e fungos pela MEV no trato gastrointestinal de peixes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…BakkeMcKellep et al 2007b;Merrifield et al, 2009;Dimitroglou et al 2010) and several studies have observed sensitivity of the gut microbiota of fish to different dietary lipid levels (Lesel et al, 1989; and different dietary plant oils (Ringø et al, 2002;Montero et al, 2006). However, to our knowledge only one study has assessed the effect of dietary SBO on the gut microbiome of fish.…”
Section: Soybean Oilmentioning
confidence: 99%
“…However, to our knowledge only one study has assessed the effect of dietary SBO on the gut microbiome of fish. In their study with Arctic charr, Ringø et al (2002) evaluated the effect of SBO on the autochthonous gut microbiota. The presence of autochthonous bacteria associated with the microvilli of fish fed the SBO enriched diet is demonstrated in Figure 7.…”
Section: Soybean Oilmentioning
confidence: 99%